The Effect of Teacher Personality Competence and School Climate on the Character of Junior High School Students in Solok Regency - Eldasisca Dwapatesty; Hadiyanto; Irsyad; Sulastri (CV. AFDIFAL MAJU BERKAH, 2022)
This research is motivated by the results of the author's observations regarding the effect of teacher personality competence and school climate on the character of junior high school students in Solok Regency which shows that it is still not good and the character of students is still low. The purpose of this study was to obtain data and information regarding (1) whether there is an effect of teacher personality competence on the character of junior high school students in Solok district, (2) whether there is an influence of school climate on the character of junior high school students in Solok district, ( 3) is there an effect of the teacher's personality competence and school climate together on the character of junior high school students in Solok Regency.This research is a correlational quantitative research with the type of